Learn & Fun Chinese Class Sebagai Sistem Pengajaran Ilmu Mandarin yang Efektif dan Efisien - Heru Wijayanto Aripradono; David Febrian (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Currently, in Indonesia and several other countries, Mandarin is the second international language after English. This is because China's economy is growing rapidly. Apart from the economic perspective, China is also a source of investment from various countries, one of which is Indonesia. The aim of this research is to create more innovative, relevant and effective solutions. This research updates the game method "Fated Hànyǔ Card". The aim of this research is to identify and analyze the influence of the "Fated Hànyǔ Card" game method in improving Mandarin language learning. This study used qualitative research methods. Data collection techniques were carried out by means of observation and interviews, the data collected was analyzed thematically. The results of the research to improve learning Mandarin, namely the Fated Hànyǔ Card game, have proven to be able to increase students' understanding in learning Mandarin because it is considered interesting and fun by students.